Astrocytes carrying LRRK2 G2019S exhibit increased levels of clusterin chaperone via miR-22-5p and reduced ability to take up α-synuclein fibrils - Alice Filippini; Giulia Carini; Alessandro Barbon; Massimo Gennarelli; Isabella Russo (Acta Neuropathologica Communications)
Abstract Accumulating evidence highlights that dysfunction of astrocyte biology might contribute to Parkinson’s disease (PD) onset and progression. Leucine-rich repeat kinase 2 (LRRK2), a gene linked to genetic and familial PD, has been reported to affect astrocytic-related functions, including the ingestion of alpha-synuclein (α-syn) aggregates. In this context, we recently showed that the extracellular chaperone clusterin (Clu) binds to and limits the uptake of alpha-syn fibrils by astrocytes. Thus, starting from these premises, we explored whether LRRK2 G2019S affects aggregated α-syn ingestion through the Clu-related pathway and the underlying molecular mechanisms. We first validated in our LRRK2 G2019S knock-in (KI) mouse strain that primary astrocytes exhibited an impaired ability to ingest fibrillary α-syn. Then, we investigated whether LRRK2 G2019S affects this pathway through the modulation of Clu. In this regard, we collected several results showing that LRRK2 regulates Clu levels in astrocytes. Specifically, brain slices and primary astrocytes from KI mice with the LRRK2 G2019S pathological mutation exhibit increased levels of Clu protein compared to their respective wild-type (WT). Accordingly, we observed an opposite effect in brain slices and primary astrocytes from LRRK2 knock-out (KO) mice in comparison to their respective WT. To gain insights into the molecular mechanism underlying LRRK2-dependent Clu modulation, we found that LRRK2 controls Clu expression at the translation level through the action of miR-22-5p. In addition, we demonstrated that treatment with miR-22-5p mimic improves the ability of LRRK2 G2019S-KI astrocytes to take up α-syn pffs. Taken together, our findings indicate that the LRRK2-Clu pathway is involved in the ingestion of a-syn fibrils and that the impairment of α-syn uptake in LRRK2 G2019S-KI astrocytes is associated to Clu levels. Future studies will allow us to understand whether the modulation of astrocytic LRRK2 G2019S-Clu pathway might attenuate the neuronal spreading of α-syn pathology in PD.